Incidence and Risk Factors for Clostridium Difficile-Associated Diarrhea Following Revision Total Hip Arthroplasty - Curtis, Gannon L.; Yokhana, Sanar S.; Samuel, Linsen T.; Higuera-Rueda, Carlos A.; Little, Bryan E.; Darwiche, Hussein L. (The Journal of Hip Surgery, 2019)
Clostridium difficile-associated diarrhea (CDAD) is a well-known cause of complications and increased hospital cost following surgery. As CDAD rates continue to be adopted as a quality metric by institutions, it is important to detect high-risk patients prior to surgery, including revision total hip arthroplasty (rTHA). This study was performed to identify the incidence and risk factors of CDAD within 30 days of rTHA. The American College of Surgeons National Surgical Quality Improvement Program (ACS-NSQIP) was accessed from 2015 to 2016 to identify rTHA procedures. Overall, 4,178 patients were included. Preoperative and perioperative variables were analyzed as potential risk factors for the development of CDAD. To compare categorical variables, Chi-square and Fisher's exact tests were used, while t-tests were used to detect differences in continuous variables. Independent risk factors for CDAD were identified using stepwise logistic regression. The rate of CDAD was found to be 0.5% (20/4,178) within 30 days of rTHA. Preoperative functional dependence (odds ratio [OR] = 3.34; p = 0.035) and dyspnea (OR = 3.80; p = 0.019), were statistically significant risk factors for the development of CDAD after rTHA. Septic revision was not a significant risk factor for CDAD (OR = 2.50; p = 0.082). The incidence of CDAD after rTHA in the United States is approximately 0.5%. Independent risk factors for CDAD include preoperative functional dependence and dyspnea. High-risk patients must be identified prior to surgery and antibiotic selection for other infections should be managed judiciously.
Keywords: Clostridium difficile; incidence; risk factors; revision; total hip arthroplasty